Analysis Income Business Farmers Paddy Ricefield Organic in Pasar Terusan Village Muara Bulian District Regency Batang Hari Jambi Province - Bangun Joko Laksono; Reno Armando; Ratna Dewi; Uliya (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the income of organic rice farming. This research was conducted in Pasar Juruan Village, Muara Bulian District, Batang Regency Day by using primary and secondary data. Sampling in this study was conducted by accidental sampling method with 40 farmers as respondents. The variables measured in this study are production, land area, number of workers, number of seeds, number of organic pesticides and organic fertilizer. Based on the results of the study, it can be concluded that the overall acceptance of organic wetland rice farming farmers in the village market canal in the district of Muara Bulian Batang Batang district amounted to Rp 281,275,000, with a total production cost of organic wetland rice farming farmers amounting to IDR 59,826,630. The income of the sample farmers in organic rice farming in the study area is Rp. 221,448,370 and an average of Rp. 5,536,209 with an R / C ratio of 4.7, then organic rice farming is feasible to be cultivated